Prediction of Antidepressant Response to Venlafaxine by a Combination of Early Response Assessment and Therapeutic Drug Monitoring - Stamm, T. J.; Becker, D.; Sondergeld, L. M.; Wiethoff, K.; Hiemke, C.; O’Malley, G.; Ricken, R.; Bauer, M.; Adli, M. (Pharmacopsychiatry, 2014)
Introduction:  Early assessment of a therapeutic response is a central goal in antidepressant treatment. The present study examined the potential for therapeutic drug monitoring and symptom rating to predict venlafaxine treatment efficacy (measured by overall patient response and remission).Methods:  88 patients were uptitrated homogenously to 225 mg/day venlafaxine. Serum concentrations of venlafaxine (VEN) and its active metabolite O-desmethylvenlafaxine (ODV) were measured at week 2. Continuous psychopathometric ratings were measured for up to 6 weeks by independent study raters.Results:  An early improvement was significantly more common in venlafaxine responders than non-responders (χ2; p=0.007). While ODV serum levels were significantly higher in responders (t test; p=0.006), VEN serum levels, sum level of VEN+ODV and the ratio of ODV/VEN levels were not. Moreover, patients who showed an early response combined with an ODV serum level above the median of 222 ng/mL were significantly more likely to achieve full response (binary logistic model; p<0.01). Sensitivity (84% for early response) and specificity (81% for combination of early response and therapeutic drug monitoring) were sufficient to qualify as a reasonable screening instrument.Conclusion:  Our results indicate that early improvement and ODV serum concentration are predictive of therapeutic outcome and can thus be used to guide use of the antidepressant venlafaxine.
Keywords: depression; early response; therapeutic drug monitoring; treatment algorithm